Taking Control: Language Professionals and Their Perception of Control when Using Language Technologies - Marshman, Elizabeth (Meta, 2014)
Language technologies (for example, computer-aided and machine translation tools) are now well established in the language industry. Unfortunately, so are questions about their advantages and drawbacks. Many of these appear to be linked to language professionals’ control over their work and working environment. We surveyed these professionals to discover how they perceive language technologies’ effect on their control over the amount of work they do, the tasks they carry out and the methods they use, the quality of the product, the relationships with clients/employers, and their remuneration. The results reveal that most current users have positive opinions of technologies overall and generally feel that these tools increase their control over their work and working environment (and particularly the quantity and quality of the work). However, hesitations remain, in particular in regard to relationships with clients/employers and remuneration.